Copyright, plagiarism and co-authorship: academic and ethical - Satur, Roberto Vilmar (2020)
Copyright, plagiarism and co-authorship are themes that arouse controversy in the academic world, especially under ethical and legal parameters.  The general objective of this research is to understand, from the perspective of copyright, non-plagiarism and co-authorship, how the use of information and its belonging to others can be made without having an unethical or anti-legal attitude, as well as demystifying self plagiarism. To that end, the research question was: “From the perspective of copyright, non-plagiarism and co-authorship, how can the use of information of his or her own and of others be used without having an unethical or anti-legal attitude?” The methodology used was bibliographic and reflection research, using qualitative arguments. As result, there is an important debate involving two problematic sides of the “same coin”. On one side, are those who produce more works, with their researches and writings, the publishers, periodicals, courses and regulatory agencies; And on the other side are those who are asked (required) to produce in quantity and quality and do not fit well to this requirement, for not having that profile, and that often resort to “sellers of academic works”, by copying parts or the work of others or repeating their work already done as something new. It is known that to meet the academic demands of production, many people use unethical subterfuges to achieve their goals, and others take advantage, creating a lucrative business. The regulatory and supervisory bodies attempt to act and inhibit such practice, such as the creation of the Copyright Law, plagiarism detection software and others. However, this practice is far from being completely eliminated. This article will discuss the unfolding of issues of copyright, plagiarism and co-authorship, instigating the academy itself to reflect not only on the students’ attitudes, but also on teachers and researchers. We conclude that not everything that seems to be a crime is so and it is necessary to review practices and requirements that try to make the researcher a producer in series of publications without relativizing the condemnation of the unethical practice of false authorship